SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2006
DOI: 10.2118/101087-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Wellbore Stability and Sand Production Prediction Study for a Multi-Field Gas Development

Abstract: This paper presents a geomechanical study on the potential of wellbore instability and sand production for a multi-field gas development in offshore Peninsular Malaysia. The objectives of the study wereto develop strategies to maintain mechanical and time-dependent stabilities of extended reach wells, andto assess sand production risk in the development wells and eliminate unnecessary downhole sand control. The data required for the study include:in-situ stresses, including magnitude and orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Geomechanical model for wellbore analysis is of utmost importance for a successful drilling program (Plumb et al, 2000) and field development plans. This geomechanical study is also important because of its adverse effects on drilling performance, and also it's potential to severely impact on both drilling schedule and budget (Wu et al, 2006). Due to the presence of overpressured formations in the Pannonian Basin, wellbore instability is often experienced.…”
Section: Wellbore Instabilitymentioning
confidence: 99%
“…Geomechanical model for wellbore analysis is of utmost importance for a successful drilling program (Plumb et al, 2000) and field development plans. This geomechanical study is also important because of its adverse effects on drilling performance, and also it's potential to severely impact on both drilling schedule and budget (Wu et al, 2006). Due to the presence of overpressured formations in the Pannonian Basin, wellbore instability is often experienced.…”
Section: Wellbore Instabilitymentioning
confidence: 99%
“…Several experimental studies on the effect of water-cut on sand production have been reported on both loose sands and intact sandtones 4,[6][7][8]22 . The study presented by Skjearstein et al 6 and Wu et al 22 are laboratory sand production experimental studies that incorporated water-cut effect on intact sandstones.…”
Section: Spe 92715mentioning
confidence: 99%
“…The study presented by Skjearstein et al 6 and Wu et al 22 are laboratory sand production experimental studies that incorporated water-cut effect on intact sandstones. Bianco and Halleck 8 and Bruno et al 4 reported the results of water-cut effect for both oil and gas flow on loose sands.…”
Section: Spe 92715mentioning
confidence: 99%
See 1 more Smart Citation